Cache Valley virus isolation from a horse in Veracruz State, Mexico - Gamaliel Ortega-Soriano; Jessica A. Plante; Veronica A. Fabela-Becerril; Ana L. Gonzalez-Perez; Mario Solis-Hernandez; Grace Rafael; Steven G. Widen; Kenneth S. Plante; Scott C. Weaver; Jose Guillermo Estrada-Franco (Frontiers in Tropical Diseases)
Cache Valley virus (CVV) was isolated from a clinically presenting horse in the Mexican Gulf region. CVV is linked to neuroinvasive disease in humans and fetal demise and defects in sheep. This is the first association between CVV and disease in horses. Implications for public and veterinary health are discussed.